2014
DOI: 10.1186/1751-0759-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Modeling students’ instrumental (mis-) use of substances to enhance cognitive performance: Neuroenhancement in the light of job demands-resources theory

Abstract: BackgroundHealthy university students have been shown to use psychoactive substances, expecting them to be functional means for enhancing their cognitive capacity, sometimes over and above an essentially proficient level. This behavior called Neuroenhancement (NE) has not yet been integrated into a behavioral theory that is able to predict performance. Job Demands Resources (JD-R) Theory for example assumes that strain (e.g. burnout) will occur and influence performance when job demands are high and job resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
53
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(67 citation statements)
references
References 72 publications
11
53
2
1
Order By: Relevance
“…The motives discussed may be a characteristic of demanding universities and programs where pressure to perform are more likely to be observed academically. The findings were consistent with previous literature that examined college students' motives for NMUPD [12,17]. Similar to our findings, a quantitative study conducted among college students found that stimulants were primarily used for studying for examinations periods such as midterms and finals [16].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The motives discussed may be a characteristic of demanding universities and programs where pressure to perform are more likely to be observed academically. The findings were consistent with previous literature that examined college students' motives for NMUPD [12,17]. Similar to our findings, a quantitative study conducted among college students found that stimulants were primarily used for studying for examinations periods such as midterms and finals [16].…”
Section: Discussionsupporting
confidence: 82%
“…For instance, the literature indicates that the primary motives for NMUPD among college students include experimentation, recreational purposes, and to increase their academic performance [11][12][13][14]. More specifically, common reasons college students reported engaging in the non-medical use of stimulants (i.e., Adderall, Vyvanse, and Ritalin) to increase performance during academic examination periods [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…The positive association between high study demands, psychological distress and self-reported PCE among University students has been empirically supported by several studies (e.g., Weyandt et al, 2009;Wolff & Brand, 2013). Another study among German University students found that self-reported PCE was associated with higher burnout scores (Wolff, Brand, Baumgarten, Lösel, & Ziegler, 2014). Taken together, these findings suggest that PCE can be seen as a way of coping with high demands and stress and, therefore, can be seen as a means-to-an-end (i.e., self-administering PCE to cope better with study demands).…”
Section: Academic Burnout and Engagement As Correlates Of Pce Usementioning
confidence: 72%
“…Although engagement was primarily studied in relation to workplace stress and burnout several studies have shown that this concept also applies to University students (Schaufeli, Salanova, González-Romá, & Bakker, 2002). If academic burnout is positively associated with PCE use (e.g., Wolff et al, 2014) and engagement with studies represents a positive student experience that is antithetical to academic burnout, then, it is sensible to expect that engagement with studies will be negatively associated with PCE use among University students. This hypothesis, however, remains to be determined by empirical evidence.…”
Section: Academic Burnout and Engagement As Correlates Of Pce Usementioning
confidence: 99%
See 1 more Smart Citation